TREATMENT OF FEMALE URETHRAL STRICTURE WITH VENTRAL-INLAY BUCCAL MUCOSAL GRAFT URETHROPLASTY: A COHORT STUDY. - Abhishek Bose; Pushpendra Kumar (Student’s Journal of Health Research Africa, 2024)
Background A rare but serious disorder that lowers quality of life and causes severe urine symptoms is called female urethral stricture disease, or USD. More successful surgical interventions are required because traditional treatments like internal urethrotomy and urethral dilation frequently have significant recurrence rates. In female patients with urethral stricture, the aim of this study was to assess the safety and efficacy of ventral-inlay buccal mucosal graft urethroplasty. Methods Twenty females with urethral stricture were included in prospective observational research. Individuals with neurogenic bladder or abnormal neurological examination results were not accepted. Cystoscopy was used to confirm the diagnosis. Following surgery, patients were monitored for 3, 6, and 12 months, during which time uroflowmetry, postvoid residual urine (PVRU), and American Urological Association (AUA) symptom scores were measured. Paired t-tests were used for statistical analysis. Results Significant surgical improvements in urinary symptoms and flow rates were shown in the study. After surgery, the average AUA symptom score dropped from 18 ± 3.5 to 4 ± 1.2 at 12 months (p < 0.001). The maximal urine flow rate (Qmax) increased from 8.5 ± 2.1 ml/s to 20 ± 3.0 ml/s (p < 0.001), and the mean PVRU dropped from 150 ± 45 ml to 20 ± 10 ml (p < 0.001). Recurrence was detected in 15% of patients, with few problems recorded. Conclusion Ventral-inlay buccal mucosal graft urethroplasty significantly improves urinary symptoms and flow rates in female patients with urethral stricture, demonstrating its effectiveness and safety with low recurrence and complication rates. Recommendations It is advised to do more studies with bigger sample sizes and longer follow-up times in order to confirm these results and create standardised treatment guidelines for female urethral stricture.